Analisis Efisiensi Pelayanan Puskesmas sekota Padang tahun 2023 dengan pendekatan Data Envelopment Analysis - Ruli Setiawan; Maizul Rahmizal; Rusy Dina (Media Riset Ekonomi Pembangunan (MedREP), 2025)
The purpose of this study is to find out the efficiency of health center services in Padang City in 2023. The method used in the study is data envelopment analysis, with two models, the first is the output-oriented VRS model and the output-oriented CRS model. The input variables used to measure this efficiency are from operational health assistance, the number of doctors, the number of midwives and nurses. While the output variables consist of outpatients, and visits by pregnant women, and the number of toddlers weighed. The results of the study with the VRS input-oriented model showed that there were 14 health centers experiencing efficiency and 10 health centers that were not efficient.